1997
DOI: 10.1021/jp972158k
|View full text |Cite
|
Sign up to set email alerts
|

Alanine Radicals:  Structure Determination by EPR and ENDOR of Single Crystals X-Irradiated at 295 K

Abstract: Single crystals of the amino acid l-α-alanine have been X-irradiated at room temperature, and the free radical formation has been studied using X-band and K-band EPR, ENDOR, and EIE (ENDOR-induced EPR) spectroscopy in the temperature interval 220−295 K. Aided by the results from EIE, as well as ENDOR from selected magnetic field positions, nine hyperfine coupling tensors were obtained and assigned to three different radicals. Room-temperature relaxation behaviors characterized by efficient W1 x and W1e and by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
161
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(181 citation statements)
references
References 44 publications
18
161
1
1
Order By: Relevance
“…It can therefore be concluded that the amino group is slightly 'skewed' from the radical plane in the radical R2 conformation. This is in line with the conclusions of Sagstuen et al, 64 who suggested a value of 7.3°, assuming a perfectly planar radical backbone. In their work, 8.3, 8.2 and 5.5 MHz were proposed for the principal values of the N4 hyperfine interaction.…”
Section: Radical R2supporting
confidence: 92%
See 3 more Smart Citations
“…It can therefore be concluded that the amino group is slightly 'skewed' from the radical plane in the radical R2 conformation. This is in line with the conclusions of Sagstuen et al, 64 who suggested a value of 7.3°, assuming a perfectly planar radical backbone. In their work, 8.3, 8.2 and 5.5 MHz were proposed for the principal values of the N4 hyperfine interaction.…”
Section: Radical R2supporting
confidence: 92%
“…At the UB3LYP/6-311G(d) level, the total spin density on the central carbon atom C2 amounts to 0.93 (0.96 with the IGLO III basis set), which is substantially higher than the previously estimated value of 0.72 reported by Sagstuen et al 64 It can therefore be expected that the hyperfine interaction will be mainly due to the methyl and amino protons. For the methyl protons, our calculations suggest comparable couplings to those obtained for radical R1, as can be seen from Table 1.…”
Section: Radical R2mentioning
confidence: 54%
See 2 more Smart Citations
“…However, it puts the detected nitrogen on an alanine molecule neighboring the radical and not on the detached ammonium, as can be seen in Figure SI-2 of the supplementary information. The H(C) dipolar coupling detected by Sagstuen et al 17 at room temperature was attributed to a nearby methyl group. Our calculations confirm this analysis: the measurements agree very well with the calculated hyperfine tensor obtained by averaging the individual proton tensors of the methyl group located just below the SAR radical (see Figure SI-2).…”
Section: Spectroscopic Identification Of A4amentioning
confidence: 85%